2020
DOI: 10.1021/acs.jpclett.0c01438
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Two-Photon Action Cross Section by Changing a Single Heteroatom Position in Fluorescent Dyes

Abstract: The optimization of nonlinear optical properties for “real-life” applications remains a key challenge for both experimental and theoretical approaches. In particular, for two-photon processes, maximizing the two-photon action cross section (TPACS), the figure of merit for two-photon bioimaging spectroscopy, requires simultaneously controlling all its components. In the present Letter, a series of difluoroborates presenting various heterocyclic rings as an electron acceptor have been synthesized and their absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…Additionally, the presence of BF 2 ‐group also increases significantly 2PA cross‐section as demonstrated by comparisons between BF 2 ‐dyes and its precursor [51] . Moreover, the 2PA properties of BF 2 ‐containing dyes can be tuned by various synthetic strategies [52,53] . For the purpose of the present study we designed three different series of dyes ( A , B , and C see Figure 1) containing the difluoroborate electron‐withdrawing moiety.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Additionally, the presence of BF 2 ‐group also increases significantly 2PA cross‐section as demonstrated by comparisons between BF 2 ‐dyes and its precursor [51] . Moreover, the 2PA properties of BF 2 ‐containing dyes can be tuned by various synthetic strategies [52,53] . For the purpose of the present study we designed three different series of dyes ( A , B , and C see Figure 1) containing the difluoroborate electron‐withdrawing moiety.…”
Section: Introductionmentioning
confidence: 94%
“…[51] Moreover, the 2PA properties of BF 2 -containing dyes can be tuned by various synthetic strategies. [52,53] For the purpose of the present study we designed three different series of dyes (A, B, and C see Figure 1) containing the difluoroborate electronwithdrawing moiety. Previously, some of us showed that structure similar to series A might yield quite large s 2PA .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to visualise, characterise and quantify biological entities, bright molecular imaging probes are needed (Yang et al, 2020a). To generate bright 2P microscopy images without causing considerable photo-damage to the sample at laser intensities required (1 GW•cm −2 at the focal plane; or ~5 mW at the objective lens), it is estimated that the 2P brightness σ 2 Φ f of the imaging agent should be more than 50 GM (Kim and Cho, 2015;Osmialowski et al, 2020). As such, breaking down the barriers to exploit NIR-II wavelengths in 2P bio-imaging involves three main challenges: (i) shifting the 2PA band of the imaging agent beyond 1000 nm, which typically involves 1PA above 500 nm; (ii) improving the 2PA crosssection σ 2 above this wavelength, typically to values >50-100 GM; and (iii) retaining a high enough fluorescence quantum yield Φ f to image tissues with high contrast.…”
Section: Introductionmentioning
confidence: 99%
“…They have been studied for applications in various areas of photochemistry due to their structure versatility and facile modifications for electron-donating abilities [ 11 , 12 , 13 ]. In general, organic compounds bearing an alkylamino group may be synthesized through a related synthetic strategy using one of the following: Heck reaction [ 14 ], Knoevenagel condensation [ 13 , 15 ], Wittig reaction [ 16 ], Suzuki-Miyaura cross-coupling reaction [ 17 ] and several different reagents, such as aryl bromides with amino substituents [ 14 ], p -aminobenzaldehydes [ 13 , 15 ] and p -aminobenzoic acid derivatives [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%